OPTIMASI PERANCANGAN ALAT PENGERING IKAN AIR TAWAR KAPASITAS 50 KG MEMANFAATKAN TENAGA SURYA DAN BIOMASA - Rendi Rendi (Universitas Lambung Mangkurat, 2016)
Kandangan city is one of the largest in the region banjarmasin dried fish, dried fish Processing in Kandangan city still quite traditional, namely only with drying fish under direct solar heat that has some shortcomings such as: a long time, need some time reversal process and less hygienic. To increase the productivity of fish farmers ate fish drier is planned sourced from solar power and biomass.The method used in this study is that the first field surveys, collect data of temperature, humidity and solar radiation in the area of research. Second, collect data levels of fish that have not been drained and dried. The field survey will be a design parameter.Based on calculations performed empirically obtained: design the most optimal solar collector is designed with a slope of 10°, 8,236 m2 collector area, drying air velocity of 1,9 m / s, 1,7 m width of the drying chamber and drying chamber area of 2,89 m2. APK most optimal design that is designed with a tube diameter of 0,028 m 0,7 m long tube tube 60° and Pr Structure 1,5 number of tube 35 and a shell diameter of 0,27 m.